2012
DOI: 10.2106/jbjs.k.00813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tourniquet Use on Blood Loss and Soft-Tissue Damage in Total Knee Arthroplasty

Abstract: The use of a tourniquet during total knee arthroplasty was effective for reducing blood loss and avoiding excessive postoperative inflammation and muscle damage. The use of a tourniquet was related to slightly more postoperative pain but did not affect postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
157
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 1 publication
7
157
2
1
Order By: Relevance
“…Tourniquet use during TKA surgery decreases total blood loss, creates a bloodless field and decreases operative time. 1 Complications reported as a consequence of tourniquet application are skin injury [skin abrasions, blisters, breaks & pressure necrosis], nerve injury, post tourniquet syndrome, Deep venous thrombosis, Postoperative pain, wound healing disorders and early infections. 2e12 Pain is one of the most important outcome measures that contribute to patient dissatisfaction after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Tourniquet use during TKA surgery decreases total blood loss, creates a bloodless field and decreases operative time. 1 Complications reported as a consequence of tourniquet application are skin injury [skin abrasions, blisters, breaks & pressure necrosis], nerve injury, post tourniquet syndrome, Deep venous thrombosis, Postoperative pain, wound healing disorders and early infections. 2e12 Pain is one of the most important outcome measures that contribute to patient dissatisfaction after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…The citation for Tai et al [11] in our study was incorrect and should have been Olivecrona et al [10]. Olivecrona and colleagues found fewer wound complications and drainage when tourniquet pressure was limited to 225-mm Hg.…”
mentioning
confidence: 79%
“…There were a total of 13 articles reviewed in the two [2,11] meta-analysis studies. Four [1,10,12,13] of the thirteen studies (31%) showed no difference in pain. Three [6,10,13] of the thirteen (23%) studies measured swelling, and two [10,13] of the studies showed no difference between patients with and without tourniquet use.…”
mentioning
confidence: 99%
“…A study by Tai and colleagues [9] has been mentioned as reference for a study showing that increased drainage has been correlated to tourniquet pressure more than 225-mm of Mercury. However, this study compared the tourniquet and non-tourniquet group with respect to blood loss, soft tissue damage, pain, swelling rehabilitation, and hospital stay.…”
mentioning
confidence: 99%
“…It does not address the correlation between tourniquet pressure and drainage. In fact, Tai et al [9] did not use a drain in their study in order to avoid excessive blood loss.…”
mentioning
confidence: 99%